PERAN PENTING GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER KEDISPLINAN SISWA DI SMAN 9 MALANG - Zainal Abidin Irfan; Moh Muslim; Muhammad Fahmi Hidayatullah (VICRATINA, 2022)
The character of discipline is a very important asset for students, where in this casediscipline is very lacking, starting from the number of students who are not able toobey school rules, which later if this is not taken immediately action will causeproblems that will arise. will interfere with the teaching and learning process.Therefore, here the researchers carried out research actions related to how theconcept, implementation, and results of the role of PAI teachers in the formation ofstudents' discipline character, here the researchers chose SMAN 9 Malang as a placefor research actions. In this case, the researcher uses descriptive qualitative method.Regarding the results obtained, the concept was carried out by emphasizing studentsto be more familiar with ubudiyah Islamiyah, and also carrying out a charactereducation program in which students were given materials related to charactereducation. Regarding the implementation, the teacher controls or supervises directlythe students, the teacher also participates in running these programs